An overview of virtual clinics in health systems: An opinion article - Mohammad Heydaryan Manesh; Aida Asghary; Ebrahim Jaafaripooyan (Tehran University of Medical Sciences, 2023)
The provision of virtual health care has currently received ample attention from health systems worldwide, due to the recent conditions and events. Many countries are trying to provide their preliminary visits and a relatively wide range of other care virtually, paving the way towards the introduction of virtual clinics. However, in many countries, this concept has not been clearly defined, and the characteristics that are necessary to use the virtual clinics are still unknown. This perspective has sought to explain the concept of virtual clinics and their characteristics with a brief review of related literature.